Koncepcja „wolnego rynku idei” i perspektywy jej dalszego rozwoju - Wacławczyk, Wiesław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Owing to the Internet the concept of a ‘free marketplace of ideas’ is thriving. Although even today it is difficult to decide unanimously whether the Miltonian principle of the self-righting process is a theory reflected in real life, or rather a ‘rhetoric myth’, it is beyond any doubt that the conviction that under the conditions of free exchange of information and opinion truth is able to triumph over falsehood still intrigues people, who feel compelled to verify this conviction over and over again. How much the ideas referred to at the beginning of this text, namely the free marketplace of ideas and self-righting process, have taken possession of the imagination of a contemporary information recipient is demonstrated by the fact that they are echoed both in the academic studies devoted to the issue of freedom of speech and in introductory, journalistic or educational publications. It seems that in the future it will be the Internet that remains one of the main instruments to verify the rightness of the self-righting process. One should not doubt that it will be a never-ending process, as predicted by Milton. One can assume though that the concept of a ‘free marketplace of ideas’ will continue to exert a significant impact on the development of international standards of free speech both in Western culture and elsewhere.